Study of clinicodermoscopic features of topical steroid damaged face patients - Kushwah, Sunayana; Namdeo, Chaitanya; Bhatia, Kailash (International Journal of Research in Dermatology, 2023)
Background: Topical steroid dependent or damaged face is an alarming upcoming entity rampant in India due to over-the-counter availability of topical corticosteroids containing products. The present study aimed to study the clinical and dermoscopic changes in patients with topical steroid damaged face and to correlate them with potency and duration of application of the TCS. Methods: 80 patients visiting the dermatology OPD & IPD at SAIMS Hospital & PG Institute, Indore, with the chief complains of redness, itching, red raised lesions, burning, swelling, photosensitivity, pigmentation; with a history of application of topical corticosteroids of any potency on face for continuous 7 days or intermittent for 15 or more days were enrolled for the study. Results: Mean age of the patients was 31.5±8.13 years. Male to female ratio was 1:9. Twelve (15.2%) patients abused TCS for more than one year. Presenting complains of the patients were redness (82.5%), itching (66.3%), hypertrichosis (47.5%), pigmentation (66.3%), burning (38.8%) and acne (28.8%). The most common dermoscopy findings i.e., unpatterned brown pigmentation (86.3%), polygonal vessels (73.8%), fine scales (52.5%), hypertrichosis (53.8%), follicular plugs (32.5%), micropustules (15%) and ivory patches (11.3%) were observed in a statistically higher proportion of cases dermoscopically Conclusions: Dermoscopy in TSDF can help dermatologists in a multitude of ways from confirming the diagnosis to differentiating from other causes of red face and predicting the approximate duration of TCS abuse.